Genomic biomarkers for cardiotoxicity in rats as a sensitive tool in preclinical studies. Issue 10 (4th April 2013) - Nishimura, Yoko; Morikawa, Yuji; Kondo, Chiaki; Tonomura, Yutaka; Fukushima, Ryou; Torii, Mikinori; Uehara, Takeki
ABSTRACT: The development of safer drugs is a high priority for pharmaceutical companies. Among the various toxicities caused by drugs, cardiotoxicity is an important issue because of its lethality. In addition, cardiovascular toxicity leads to the attrition of many drug candidates in both preclinical and clinical phases. Although histopathological and blood chemistry examinations are the current gold standards for detecting cardiotoxicity in preclinical studies, the large number of withdrawals from clinical studies owing to safety problems indicate that a more sensitive tool is required. We recently identified 32 genes that were candidate genomic biomarkers for cardiotoxicity in rats. Based on their functions, the present study focused on 8 of these 32 genes ( Spp1, Fhl1, Timp1, Serpine1, Bcat1, Lmcd1, Rnd1 and Tgfb2 ). Diagnostic accuracy for the genes was determined by a receiver‐operating characteristic (ROC) analysis using more cardiotoxic and non‐cardiotoxic compounds. In addition, an optimized support vector machine (SVM) model that was composed of Spp1 and Timp1 was newly constructed. This new multi‐gene model exhibited a much higher diagnostic accuracy than that observed for plasma cardiac troponin I (cTnI), which is one of the most useful plasma biomarkers for cardiotoxicity detection. Furthermore, we determined that this multi‐gene model could predict potential cardiotoxicity in rats in the absence of any cardiac histopathological lesions or elevations of plasma cTnI. Overall, this multi‐gene model exhibited advantages over classic tools commonly used for cardiotoxicity evaluations in rats. Our current results suggest that application of the model could potentially lead to the production of safer drugs. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Cardiotoxicity is an important issue in drug development. In the present study, we focused on 8 genes ( Spp1, Fhl1, Timp1, Serpine1, Bcat1, Lmcd1, Rnd1 and Tgfb2 ) as candidate genomic biomarkers for cardiotoxicity in rats, and constructed an optimized support vector machine (SVM) model that was composed of Spp1 and Timp1 . This multi‐gene model exhibited advantages over classic tools commonly used for cardiotoxicity evaluations in rats, and the application of the model could potentially lead to the production of safer drugs.